Getting into character: Narrative form, motivation and Treme's Harley Watt. (September 2019) - Harriss, Chandler
This essay explores the utility of the formalist concept of motivation as a way to interrogate the textual and cultural operation of a TV character, Harley Watt from HBO's Treme (2010–2013). Peeling the layers of character construction reveals how signs convey meaning and confine interpretation. This analytic process highlights how performers and character connect, in this instance, with how the casting of singer-songwriter Steve Earle as a musician with a social conscience imports knowledge of him, his music and history. Ultimately, this essay contributes to the body of research that explores characters as creative and cultural constructs.